Acute toxicity of dichlorvos on fingerling European catfish, Silurus glanis - Ural, M. S.; Koprucu, S. Simsek (Springer, 2006)
[Abstract Not Available]
Keywords: Pyrethroid Deltamethrin; Cyprinus-Carpio; Pesticide; Fossilis; Larvae